2019
DOI: 10.3390/en12112120
|View full text |Cite
|
Sign up to set email alerts
|

Modeling an Alternate Operational Ground Source Heat Pump for Combined Space Heating and Domestic Hot Water Power Sizing

Abstract: This study developed an alternate operational control system for ground source heat pumps (GSHP), which was applied to determine combined space heating and domestic hot water (DHW) power equations at design temperature. A domestic GSHP with an alternate control system was implemented in a whole building simulation model following the heat deficiency for space heating based on degree minute counting. A simulated GSHP system with 200 L storage tank resulted in 13%–26% power reduction compared to the calculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…The performance of GSHP and AWHP in renovated residential buildings has already been studied in many scientific papers. The results of this study confirm the better functioning of the GSHP that is shown by D'Agostino et al [42], Fadejev et al [46] and Ahmed et al [40]. Properly sized heat pump systems with energy piles can have overall system SCOP values higher than 4.5, while some case studies have reported only half of such SCOP values.…”
Section: Simulation Results Of the Reference Buildingsupporting
confidence: 87%
See 1 more Smart Citation
“…The performance of GSHP and AWHP in renovated residential buildings has already been studied in many scientific papers. The results of this study confirm the better functioning of the GSHP that is shown by D'Agostino et al [42], Fadejev et al [46] and Ahmed et al [40]. Properly sized heat pump systems with energy piles can have overall system SCOP values higher than 4.5, while some case studies have reported only half of such SCOP values.…”
Section: Simulation Results Of the Reference Buildingsupporting
confidence: 87%
“…Altogether, three occupants were considered as the average number of inhabitants in the building. The consumption profile of domestic hot water was taken from the study of domestic hot water use in Finnish residential buildings [39,40]. The calculations did not include the electrical heater of the sauna and other electrical appliances that are not specified in Finnish energy efficiency calculation rules.…”
mentioning
confidence: 99%
“…So far, the application and renovation of WHSP mainly concentrate on the optimization of heat exchangers, water pumps, the overall system, and economic frictional head loss. Most mathematical models are built to optimize the following items: optimization parameters, control forms, costs, and feasibility of investment and construction [22][23][24][25][26][27][28]. For the surface WSHP system, there should exist an optimal operating condition for the chilled water circulating system, cooling water circulating system, refrigerant circulating system and transmission pipes, and heat exchangers, under which the system could operate with the minimum energy consumption.…”
Section: Introductionmentioning
confidence: 99%